PERCENTAGE OF STUDENTS’ LEARNING DIFFICULTIES IN BUFFER SOLUTION LEARNING MATERIAL - Pani Pransiska Putri (Jurnal Pembelajaran Sains, 2022)
Student learning outcomes that still need to be higher or that many students need to achieve maximum completeness in the buffer solution material are caused by the inability of students to understand the questions. This study aims to determine the percentage of senior high school students' learning difficulties in the buffer solution material of chemistry. The research method used is bibliometric analysis by collecting literature results from Google Scholar with the keywords: Learning Difficulty, Buffer Solution. The results showed that the level of students' learning difficulties ranged from 67.33% to 85.85%, internal factors causing learning difficulties included motivation and interest, and external factors, including family, teachers and school. Thus, it is hoped that students will deepen their knowledge about buffer solutions and hold discussions with the teacher and their friends to overcome this problem of learning difficulties.